An Action Research on the Impact of Podcasts in Grammar Learning of Elementary Students - Nan, Ja; Lan Nai Ciang (International Journal of Language and Literary Studies, 2024)
With technology development, language studies use online resources as authentic materials for more engaging and effective language learning. With this perception, the researchers investigated how podcasts can be employed as authentic learning facilities for English learners specifically on the mobility and exclusivity of this material in teaching verb tense and form aspects. The researchers conducted a 40-item language test as a pretest and posttest utilizing podcasts for grade 6 students. The participants’ behaviours were also observed to have in-depth information. Whereas, the collected responses from the questionnaire on the students’ attitudes towards the use of podcasts were employed to provide an understanding of the factors that might have impacted the study. The results indicate that utilizing podcasts in grammar lessons has a positive impact on student’s grammar knowledge. Additionally, the observed behaviors manifested while using the podcasts in class affirmed learners’ interests and their cooperation although there are times they expressed boredom and restlessness due to long periods of listening. Eventually, they expressed enjoyment and satisfaction in their participation in grammar learning with podcasts. It is suggested that teachers should use short podcasts that are appropriate to the target grammar to enhance students’ motivation.